1966
DOI: 10.1084/jem.124.4.585
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Acquired Resistance in Mouse Typhoid

Abstract: Experiments in vitro comparing normal mouse peritoneal macrophages with cells from Salmonella typhimurium-infected mice have shown that the "immune" macrophages have conspicuously enhanced microbicidal properties. Whereas normal macrophages could inactivate only 50 to 60% of intracellular S. typhimurium pretreated with immune serum, cells from infected animals killed virtually all ingested organisms and did so at an accelerated rate. Macrophages from Listeria monocytogenes-infected mice were shown to possess s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
129
0
1

Year Published

1972
1972
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(142 citation statements)
references
References 22 publications
(34 reference statements)
12
129
0
1
Order By: Relevance
“…The effect of antibodies in mouse salmonellosis is restricted in several ways: (i) it is clearcut against IP but negligible against IV challenge Jenkin & Rowley, 1963;Blanden et al, 1966); (ii) it is almost exclusively mediated by the IgM class of anti-Salmonella antibodies (Saxkn & Miikelii, 1982;Saxkn et al, 1984b); and (iii) as shown in the present study, their effect is restricted to the very early phase of the infection. The data presented here help to explain each of these restrictions by showing where in the infectious process the antibodies intervene.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The effect of antibodies in mouse salmonellosis is restricted in several ways: (i) it is clearcut against IP but negligible against IV challenge Jenkin & Rowley, 1963;Blanden et al, 1966); (ii) it is almost exclusively mediated by the IgM class of anti-Salmonella antibodies (Saxkn & Miikelii, 1982;Saxkn et al, 1984b); and (iii) as shown in the present study, their effect is restricted to the very early phase of the infection. The data presented here help to explain each of these restrictions by showing where in the infectious process the antibodies intervene.…”
Section: Discussionmentioning
confidence: 87%
“…Both cellular and humoral immunity play a role in the defence but their relative contributions are still under debate (Levine & Hornick, 1981). The route of infection influences the course of the infection, but we do not know, for example, why intraperitoneally (IP) induced infection is more easily prevented by antibodies than is infection after intravenous (IV) challenge Jenkin & Rowley, 1963;Blanden et al, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…I N T R 0 D U C T I 0 N Whether salmonellae increase or decline in number within macrophages after phagocytosis, a factor crucial to the outcome of infection with these facultative intracellular parasites (Jenkin & Rowley, 1963;Blanden et al, 1966), depends on the balance between bacterial division and death rates in the intracellular environment. Studies with macrophages in vitro show that virulent salmonellae are more capable than avirulent organisms of increasing intracellularly (Furness, 1958 ;Furness & Ferreira, 1959 ;Jenkin & Benacerraf, 1960) and that macrophages from immune animals are better able to restrict intracellular proliferation than those from susceptible animals (Jenkin & Benacerraf, 1960;Blanden, 1968;Maier & Oels, 1972).…”
mentioning
confidence: 99%
“…Furthermore, macrophages activated by listeria infection also inhibit intracellular growth of Salmonella typhimurium (Blanden, Mackaness & Collins, 1966) and Candida albicans (Marra & Balish, 1974). Thymus-derived (T) lymphocytes are required for activation of macrophages both in vivo and in vitro (Lane & Unanue, 1972;North, 1g73a;Cole, 1975).…”
mentioning
confidence: 99%